Method for enhancing domain wall current in ferroelectric film

BiFeO3 film was prepared by pulsed laser deposition and the head-to-head charged domain wall was constructed using PFM and CAFM technology, which solved the problem of spontaneously existing charged domain walls in ferroelectric materials, and achieved the enhancement and conduction of domain wall current in ferroelectric films. Improved performance provides new ideas and application prospects for the research of nano-ferroelectric materials.

CN119173126APending Publication Date: 2024-12-20HUAIYIN INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311610313.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-29
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The prior art is difficult to exist spontaneously in ferroelectric materials and reconstruct the charged domain walls in real time, and the position is fixed in semiconductors using doping or ion implantation methods, so it is impossible to achieve dynamic control of nano-scale conductive channels, and the characterization technology is complex and expensive.

Method used

BiFeO3 film containing oxygen vacancy was prepared by pulsed laser deposition. PFM and CAFM characterization technology were used to construct head-to-head charged domain walls under the action of electric fields to achieve enhanced domain wall current.

Benefits of technology

Simple and efficient construction of stable charged domain walls within an area of ​​8μm2 provides a new idea for research on oxygen vacancy in nanoferroelectric materials. It is suitable for wiring and flexible electronic skin in electronic devices, and has good conductivity and movability sex.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119173126A_ABST
    Figure CN119173126A_ABST
Patent Text Reader

Abstract

The invention discloses a method for enhancing domain wall current in a ferroelectric film, which comprises the following steps: preparing a BiFeO3 film containing oxygen vacancies through a pulsed laser deposition method; a lattice structure of the film is obtained through an X-ray diffraction method; pFM is utilized to characterize the thin film, and the morphology and spontaneous domain structure of the thin film are obtained; characterizing the thin film by means of CAFM, and observing whether domain wall current exists or not; applying a direct-current voltage to the PFM probe, scanning the film from two sides to the middle in opposite directions, and forming a head-to-head domain wall in the middle area by using an electric field at the tail part of a needle tip; domain wall current is obtained through CAFM characterization, and it is proved that construction of the head-to-head domain wall is an effective method for enhancing the domain wall current. A head-to-head charged domain wall is constructed by using a needle point electric field, the method is simple and effective, and the conductive channel can be used for wiring in a microelectronic circuit and ferroelectric memory devices such as a memristor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of micro-nano structures, and in particular to a method for enhancing domain wall current in a ferroelectric film. Background Art

[0002] Domain walls in ferroelectrics are the hubs of topological defects, where charged domain walls have metal-like conductivity. According to theoretical predictions, the electromechanical response of ferroelectrics is enhanced when the density of charged domain walls increases. Charged domain walls represent isolated conductive channels, where the current is confined in nanoscale sheets by insulating domains, and their functionality can be integrated into nanodevices. In addition, unlike traditional heterojunctions, charged domain walls can be displaced inside dielectrics under the action of electric fields, which is of great significance for future electronic circuits.

[0003] Ferroelectric materials have two symmetrically equivalent ground states, each with a stable remnant polarization that can be flipped back and forth under the action of an electric field. Regions with the same polarization form domains, and regions with different polarizations are separated by domain walls. Domain walls without net bound charge are called neutral domain walls (NDW), and their polarization directions are connected end to end at the domain wall without transitions; domain walls carrying bound charges are called charged domain walls (CDW), and their polarization components transition at the domain wall, violating the electrostatic compatibility condition. The formation energy of charged domain walls is very high, which is not conducive to their spontaneous existence in ferroelectric materials, which poses a challenge to the preparation of samples with spontaneously existing charged domain walls.

[0004] Currently, there are precedents for creating charged domain walls by phase-change cooling materials under strong electrical bias, but this technology is not feasible when seeking real-time reconfigurability in working devices. In addition, the concentration of charged carriers in semiconductors is controlled by doping or ion implantation, but their positions in semiconductor crystals are determined by the manufacturing process and cannot be moved. From a characterization perspective, the effect of oxygen vacancies on the formation of charged domain walls can be observed using a high-resolution scanning transmission electron microscope, but this characterization instrument is expensive and the characterization technology is very difficult. Summary of the invention

[0005] Purpose of the invention: The purpose of the present invention is to provide a simple and effective method for realizing domain wall current enhancement in ferroelectric thin films.

[0006] Technical solution: The method for enhancing domain wall current in a ferroelectric thin film of the present invention comprises:

[0007] S1: Preparation of BiFeO3 thin films containing oxygen vacancies by pulsed laser deposition;

[0008] S2: The lattice structure of the film is obtained by X-ray diffraction; the film is characterized by PFM (piezoresponse force microscopy) to obtain its morphology and spontaneous domain structure; the film is characterized by CAFM (conductive atomic force microscopy) to observe whether there is domain wall current;

[0009] S3: Apply a DC voltage to the PFM probe and scan the film from both sides to the middle in opposite directions, using the electric field at the tip tail to form a head-to-head domain wall in the middle area;

[0010] S4: The domain wall current was obtained by CAFM characterization, demonstrating that constructing head-to-head domain walls is an effective way to enhance the domain wall current.

[0011] Furthermore, in step S1, the BiFeO3 film containing oxygen vacancies is a SrTiO3(001) / SrRuO3 / BiFeO3 sandwich structure, which is made by sequentially depositing a SrRuO3 layer and a BiFeO3 layer on the SrTiO3(001) surface by pulsed laser deposition.

[0012] Furthermore, after the deposition process of the SrTiO3(001) / SrRuO3 / BiFeO3 sandwich structure is completed, the temperature is directly cooled to room temperature without introducing an oxygen atmosphere at 1 atmosphere pressure to ensure that the film contains oxygen vacancies.

[0013] Furthermore, the parameters of the pulsed laser deposition method are: laser energy 56mJ, pulse number 2000, temperature 680°C, oxygen pressure 15Pa for the SrRuO3 layer; laser energy 81mJ, pulse number 2500, temperature 690°C, oxygen pressure 18Pa for the BiFeO3 layer.

[0014] Furthermore, the thickness of the SrRuO3 layer is 20-30 nm, and the BiFeO3 is a single crystal thin film with a thickness of 30-40 nm. The thickness of SrRuO3 and BiFeO3 is moderate, which makes it easier to perform subsequent writing operations of the needle tip electric field.

[0015] Further, in step S2, the PFM and CAFM needle tips are provided with a Pt / Ir conductive coating.

[0016] Furthermore, in step S2, when PFM is used for characterization, the driving frequency of the PFM tip in the vertical direction is 0.33-0.36 MHz, and the driving frequency of the PFM tip in the horizontal direction is 0.66-0.77 MHz.

[0017] Furthermore, in step S3, it is assumed that A and B are two adjacent rectangular areas in the film, with a gap in the middle, denoted as M, and the width of the gap is between a few nanometers and tens of nanometers; the scanning direction of the first step is from A to M, and the scanning direction of the second step is from B to M. In this way, the electric field at the tail of the needle tip concentrates the charged oxygen vacancies and bound charges at the boundary of the rectangular scanning area, constructing a head-to-head charged domain wall.

[0018] Furthermore, when writing, the voltage applied by the PFM tip was -6V, and the slow scanning speed was 0.5-0.6μm / s. The PFM technology was used to characterize the writing results. In addition to indicating that the polarization was reversed, it was also observed that the morphology was almost unchanged, that is, no electrochemical reaction occurred, and the sample was intact.

[0019] Furthermore, in steps S2 and S4, the applied voltage of CAFM is much smaller than the coercive voltage of the film, so that no polarization reversal occurs during the CAFM current measurement process, and the measured domain wall current does not include the contribution of polarization reversal. For example, during the CAFM measurement process, the bias voltage applied to the needle tip can be +1.0V, which is much smaller than the coercive voltage of the ferroelectric film, 3V.

[0020] The working principle of the present invention is:

[0021] A DC voltage is applied to the PFM tip, and the tip electric field generated during the scanning process flips the polarization. The process is divided into two steps of scanning, and the direction of the slow scan in each step is on the same line but in opposite directions. The electric field at the tail of the tip can concentrate the charged oxygen vacancies at the boundary of the scanning area in each step, thereby constructing a head-to-head charged domain wall. In CAFM scanning, the tip bias is +1.0V, which is less than the coercive voltage to ensure that the measured current is not the current generated by polarization reversal.

[0022] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0023] (1) Capable of measuring 8 μm 2 The construction of head-to-head charged domain walls is achieved by two steps of scanning in opposite directions within the area, which is simple and effective;

[0024] (2) Using electric fields to drive the movement of defective ions provides a new approach to the study of oxygen vacancies in nano-ferroelectric materials;

[0025] (3) The constructed charged domain wall is stable, and its good conductivity can be used for wiring in electronic devices. Its mobility has application prospects in emerging and advanced fields such as ferroelectric random access memory and flexible electronic skin. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1It is a flowchart of a method for enhancing domain wall current in a ferroelectric thin film provided by an embodiment of the present application;

[0027] Figure 2 is the XRD pattern of the film in the embodiment of the present application;

[0028] Figure 3 is the PFM piezoelectric loop of the film in the embodiment of the present application, wherein Figure 3 (a) is the phase diagram, Figure 3 (b) is the amplitude diagram;

[0029] Figure 4 is a spontaneous state diagram of the film in the embodiment of the present application, wherein Figure 4 (a) is the morphology diagram. Figure 4 (b) is the CAFM diagram. Figure 4 (c) is the out-of-plane PFM amplitude diagram. Figure 4 (d) is the in-plane PFM amplitude diagram. Figure 4 (e) is the out-of-plane PFM phase diagram. Figure 4 (f) in the figure is the in-plane PFM phase diagram;

[0030] Figure 5 is a schematic diagram of the lattice of the film in the polarized state in the embodiment of the present application, wherein Figure 5 (a) is the spontaneous polarization. Figure 5 (b) is the electric field at the right end of the needle tip. Figure 5 (c) in the figure shows an out-of-plane electric field. Figure 5 (d) in the figure shows the electric field at the left end of the needle tip;

[0031] Figure 6 : is a charged domain wall constructed by the PFM tip electric field and a CAFM image in the embodiment of the present application, wherein Figure 6 (a) and (b) are the morphology images before and after the current measurement, respectively. Figure 6 (c) is the CAFM diagram. Figure 6 (d) and (e) are the out-of-plane PFM amplitude diagrams before and after the current measurement, respectively. Figure 6 (f) in Figure 6 The data in the area corresponding to the cross-section in (c) and (e) are Figure 6 (g) and (h) are the out-of-plane PFM phase diagrams before and after the current measurement, respectively. DETAILED DESCRIPTION

[0032] The present invention will be further described below in conjunction with the accompanying drawings.

[0033] like Figure 1 As shown, a method for enhancing domain wall current in a ferroelectric thin film specifically comprises the following steps:

[0034] S1. Prepare a BiFeO3 film containing oxygen vacancies. Specifically, a SrRuO3 layer and a BiFeO3 layer are sequentially deposited on a SrTiO3 (001) substrate by pulsed laser deposition. After the deposition process is completed, the temperature is directly lowered to room temperature without introducing an oxygen atmosphere at 1 atmosphere to ensure that the film contains oxygen vacancies. The prepared film contains defective ions and no impurities.

[0035] The pulse laser deposition method uses a stoichiometric BiFeO3 ceramic target. The deposition conditions are shown in Table 1. The pulse laser is a laser with a wavelength of 248nm emitted by a KrF excimer laser. The laser energy for depositing SrRuO3 and BiFeO3 is 56mJ and 81mJ respectively. The substrate temperature is 680℃ and 690℃ respectively. The oxygen pressure is 15Pa and 18Pa respectively. The film samples containing defective ions and no impurities are obtained while still ensuring the quality. The thickness of SrRuO3 is 20-30nm, and the thickness of BiFeO3 is 30-40nm. The thickness is moderate, so it will be easy to write the needle tip electric field in the subsequent step S3.

[0036] Table 1 Pulsed laser deposition parameters

[0037]

[0038] After the BiFeO3 film is deposited, it is cooled to room temperature under an oxygen pressure of 18Pa.

[0039] S2. The lattice structure of the film is obtained by X-ray diffraction. The film is characterized by PFM to obtain its morphology and spontaneous domain structure. The film is characterized by CAFM to observe whether there is domain wall current.

[0040] like Figure 2 As shown, X-ray diffraction (XRD) was used to perform θ-2θ scanning on the film sample to achieve structural characterization. The results proved the epitaxial structure of SrTiO3 / SrRuO3 / BiFeO3. The lattice constant calculated from the out-of-plane (002) peak showed that the BiFeO3 film had a rhombohedral phase structure.

[0041] like Figure 3 As shown, the PFM piezoelectric loop of the sample was characterized using the “piezoelectric-hysteresis” mode to illustrate the ferroelectricity of the film. Figure 3 The 180° change in the PFM phase diagram shown in (a) indicates that the polarization has flipped. Figure 3 The butterfly-shaped PFM amplitude diagram shown in (b) gives the coercive field of the BiFeO3 film as ±3.8V, which is very symmetrical, indicating that the sample has good ferroelectric properties.

[0042] like Figure 4As shown in (a) in the figure, the film was characterized by atomic force microscopy. The roughness of the 2D morphology of the film was 0.8nm, and the flatness of the film was good, indicating that the quality of the prepared film was good. The individual protrusions and depressions in the morphology image indicate that the prepared high-quality single crystal film contains oxygen vacancy defects. The domain structure of the film was characterized by vector PFM technology. The PFM tip had a Pt / Ir conductive coating. The tip driving frequencies of the PFM in the vertical and horizontal directions were 0.33~0.36MHz and 0.66~0.77MHz, respectively. Vector PFM characterization was obtained, respectively. Figure 4 The out-of-plane PFM amplitude diagram shown in (c) Figure 4 (d) shows the in-plane PFM amplitude diagram, Figure 4 The out-of-plane PFM phase diagram shown in (e) and Figure 4 (f) shows the in-plane PFM phase image. The out-of-plane phase has both dark and bright contrasts, indicating that the vertical polarization is both upward and downward, and the corresponding in-plane phase image is more fragmented. This is consistent with the conclusion that the lack of oxygen in the sample during growth leads to the presence of oxygen vacancy defect ions, because if there is no oxygen vacancy, all polarization directions in the ferroelectric layer should point downward.

[0043] like Figure 4 As shown in (b), CAFM is used to characterize the film and obtain the current image. The uniform contrast indicates that the film has no domain wall current in the spontaneous state.

[0044] S3. Apply a DC voltage to the PFM probe, scan the film from both sides to the middle in opposite directions, and use the electric field at the tail of the needle tip to form a head-to-head domain wall in the middle area.

[0045] Applying a DC voltage to the PFM tip generates a tip electric field. The tip electric field scans the film to flip the polarization direction. The slow scanning speed is 0.5 to 0.6 μm / s. Figure 5 Given in the figure, the out-of-plane electric field polarizes the Figure 5 The four spontaneous directions shown in (a) are reduced to Figure 5 As shown in (c), the in-plane electric field further orients the polarization uniformly, as shown in Figure 5 As shown in (b) and (d) in .

[0046] Figure 5 The illustration in the middle of the lower part shows the process of constructing a head-to-head domain wall through the tip electric field. In the figure, A and B are adjacent areas in the film, separated by a gap M with a width of about 30nm; area A in the film is scanned with a preset -6V rectangular pattern from A to M; then area B of the film is scanned with a -6V rectangular pattern from B to M; in this way, a head-to-head polarization distribution can be formed in the M area.

[0047] S4. The writing result is characterized by PFM to obtain the constructed head-to-head domain wall, and the current enhancement of the head-to-head charged domain wall is proved by CAFM characterization.

[0048] like Figure 6 , PFM was used to characterize the film's morphology after polarization over a larger area including the writing area ( Figure 6 (a) and (b)) and domain structure ( Figure 6 The changes in (d)-(e), (g)-(h)) in the figure prove that the current of the head-to-head charged domain wall is enhanced ( Figure 6 Specifically, atomic force microscopy was used to characterize the polarization before ( Figure 6 (a) in the middle), and ( Figure 6 The morphology of (b) in the figure shows that no electrochemical reaction has occurred. The sample is intact and does not affect the current measurement. The results of writing are characterized by PFM. In addition to indicating that the polarization has been reversed, the out-of-plane amplitude diagram ( Figure 6 The dark contrast in the middle region of (d) realizes the construction of head-to-head domain walls. Repeating the steps in S3 will produce similar head-to-head (or tail-to-tail) domain wall results. CAFM image ( Figure 6 (c) in the figure clearly shows the current signal. By comparing the out-of-plane amplitude and phase diagram, it can be determined that the domain wall is conducting. In order to quantitatively give the current data, the corresponding diagram of the domain wall position and the current signal is intercepted ( Figure 6 In (f)), we can see that the domain wall width is about 50nm and the current is about 25pA.

[0049] According to the polarization distribution of charged domain walls, it is possible to write, erase and recreate charged domain walls with metallic conductivity in wide bandgap semiconductors by using polarized charges as quasi-dopants to change the concentration of charge carriers. Experiments have shown that high-density charged domain wall patterns are controllably established in BiFeO3 single crystal films, which makes it possible to use charged domain walls in devices such as memristors. These provide new ideas for the study of conductive channels in nano-ferroelectric materials and provide experimental basis for theoretical research on reconfigurable domain wall electronics.

[0050] The present invention can be applied to advanced fields such as ferroelectric random access memory, resistive memory devices, and microelectronic device wiring. For example, the operation of the present invention can successfully construct a charged domain wall, and while enhancing the conductivity of the domain wall, it can achieve non-destructive reading of the domain wall signal. For another example, the charged domain wall in the BiFeO3 film moves, and the position of the domain wall movement can be controlled by the electric field to achieve the purpose of wiring at any position in the device.

Claims

1. A method for enhancing domain wall current in a ferroelectric thin film, characterized in that: include: S1: Preparation of BiFeO3 thin films containing oxygen vacancies by pulsed laser deposition; S2: Obtain the lattice structure of the film by X-ray diffraction; characterize the film by PFM to obtain its morphology and spontaneous domain structure; characterize the film by CAFM to observe whether there is domain wall current; S3: Apply a DC voltage to the PFM probe and scan the film from both sides to the middle in opposite directions, using the electric field at the tip tail to form a head-to-head domain wall in the middle area; S4: Enhanced domain wall current obtained by CAFM characterization.

2. The method for enhancing domain wall current in a ferroelectric thin film according to claim 1, characterized in that: In step S1, the BiFeO3 film containing oxygen vacancies is a SrTiO3 (001) / SrRuO3 / BiFeO3 sandwich structure, which is made by sequentially depositing a SrRuO3 layer and a BiFeO3 layer on the SrTiO3 (001) surface by pulsed laser deposition.

3. The method for enhancing domain wall current in a ferroelectric thin film according to claim 2, characterized in that: After the deposition process of the SrTiO3(001) / SrRuO3 / BiFeO3 sandwich structure is completed, the temperature is directly cooled to room temperature without introducing an oxygen atmosphere at 1 atmosphere to ensure that the film contains oxygen vacancies.

4. The method for enhancing domain wall current in a ferroelectric thin film according to claim 2, characterized in that: The parameters of the pulsed laser deposition method are: laser energy 56mJ, pulse number 2000, temperature 680°C, oxygen pressure 15Pa for the SrRuO3 layer; laser energy 81mJ, pulse number 2500, temperature 690°C, oxygen pressure 18Pa for the BiFeO3 layer.

5. The method for enhancing domain wall current in a ferroelectric thin film according to claim 2, characterized in that: The thickness of the SrRuO3 layer is 20 to 30 nm; the BiFeO3 is a single crystal thin film with a thickness of 30 to 40 nm.

6. The method for enhancing domain wall current in a ferroelectric thin film according to claim 1, characterized in that: In step S2, the PFM and CAFM tips are provided with a Pt / Ir conductive coating.

7. The method for enhancing domain wall current in a ferroelectric thin film according to claim 1, characterized in that: In step S2, when PFM is used for characterization, the driving frequency of the PFM tip in the vertical direction is 0.33-0.36 MHz, and the driving frequency of the PFM tip in the horizontal direction is 0.66-0.77 MHz.

8. The method for enhancing domain wall current in a ferroelectric thin film according to claim 1, characterized in that: In step S3, it is assumed that A and B are two adjacent rectangular areas in the film, with a gap in the middle, denoted as M; the scanning direction of the first step is from A to M, and the scanning direction of the second step is from B to M. In this way, the electric field at the tail of the needle tip concentrates the charged oxygen vacancies and bound charges to the boundary of the rectangular scanning area, constructing a head-to-head charged domain wall.

9. The method for enhancing domain wall current in a ferroelectric thin film according to claim 8, characterized in that: During writing, the voltage applied by the PFM tip is -6V, and the slow scanning speed is 0.5 to 0.6 μm / s.

10. The method for enhancing domain wall current in a ferroelectric thin film according to claim 1, characterized in that: In steps S2 and S4, the applied voltage of CAFM is much smaller than the coercive voltage of the film, so that no polarization reversal occurs during the current measurement by CAFM, thereby ensuring that the measured domain wall current does not include the contribution of polarization reversal.